Here's the question you clicked on:
recon14193
solve a log
\[\log_{a}x+\log_{a}x-2=\log_{a}x+4 \]\ \[\log_{a}x(x-2)=\log_{a}x+4\] that is my work so far I do not know how to convert to exponential
I am wondering if I divide by \[\log_{a}x+4\] and then have it equal to zero which means my final answer is just 1
assuming the right hand side is \(\log_a(x+4)\) then your last job is to solve \[x(x-2)=x+4\]
so the logs just drop out
log is a "one to one function" so if \[\log(A)=\log(B)\] then \(A=B\)
ok I guess but I dont really understand
ok suppose instead of log, you had \[f(x)=2x+4\]
if you were told that \[2a+4=2b+4\] then you would know that \(a=b\) right?
it is the same with the log if \(\log(x)=\log(y)\) then you know \(x=y\)
in other words, as in your example, the only way for \(\log(x^2-2x)\) to be equal to \(\log(x+4)\) is if \(x^2-2x=x+4\)
oh I see now so if i understand correctly it is because we know they must be equal that the fact that it is a log of each does not matter because no matter what they yield the same result
Thank you I appreciate your help
if i know \(\log(x)=\log(5)\) then i know that \(x=5\) i cannot be anything else